PERSEPSI PELAKU KEKERASAN DALAM RUMAH TANGGA TERHADAP UU PKDRT NO 23 TAHUN 2004 - Jamilah, Jamilah; Adicahya, Akmal (Fakultas Syariah, 2014)
The Domestic Violence Act of Indonesia has been applied for 10 years. However, it seems this act does not reduce significantly the practice of domestic violence. Lawrence Friedman emphasizes that there is legal culture that influences legal system. It means that the acceptance of citizen influences the quality of legal system. This research shows that the offenders of domestic violence accept the regulation. Moreover, they consider this regulation as good act to implement. However, there are several factors that make them still practice violence toward their family. Less knowledge, public acceptance and psychological condition contribute to the level of obedience before the law. Therefore, citizens need a good and massive socialization from government about this regulation.